2008
DOI: 10.3354/meps07239
|View full text |Cite
|
Sign up to set email alerts
|

Active migration of wild Atlantic salmon Salmo salar smolt through a coastal embayment

Abstract: Migration patterns of wild Atlantic salmon Salmo salar smolt were examined in a coastal embayment in the Gaspé peninsula of Québec, Canada. Twenty-four smolt in 2005 and 30 in 2006 were tagged with coded ultrasonic transmitters, and their migration throughout the bay was monitored using an array of fixed VR2 hydrophone receivers. Migration patterns were complex, with some smolt taking a direct route through the coastal embayment and others repeatedly changing direction over short spatial and temporal scales. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 28 publications
(31 reference statements)
7
49
2
1
Order By: Relevance
“…However, other studies have demonstrated that water currents are not systematically used as an orientation cue, because smolts often show random movements compared to the water current direction [27,31]. It has also been suggested that positive salinity gradients may be one of the key factors for seaward movements [6,26]. Our results support that post-smolts may exploit variation in salinity cues for navigation purposes.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…However, other studies have demonstrated that water currents are not systematically used as an orientation cue, because smolts often show random movements compared to the water current direction [27,31]. It has also been suggested that positive salinity gradients may be one of the key factors for seaward movements [6,26]. Our results support that post-smolts may exploit variation in salinity cues for navigation purposes.…”
Section: Discussionsupporting
confidence: 78%
“…The smolts normally show rapid and directed seaward movements in a fjord system, and during the seaward movements little is known about visits to freshwaters and brackish waters. Swimming speeds normally increase with the distance from the natal river [6,12]. However, in the present study, the swimming speeds became slower as the post-smolts moved further away from their home river.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Other laboratory experiments have found no period of acclimation occurred for smolts upon reaching salt water (Moore et al 1995). It is, however, possible that fish use tidal movements to minimize energetic costs, especially because this is the period of migration during which smolts are thought to transition from passive to active migration (Hedger et al 2008;Martin et al 2009). Further investigation of diurnal and tidal factors that influence behavior and survival on localized spatial and temporal scales could provide an improved understanding of those mechanisms and might have implications for strategic stocking of hatchery-reared smolts.…”
Section: Atlantic Salmon Smolts During Estuary Migrationmentioning
confidence: 99%